Conservation agriculture enhances crop productivity and soil carbon fractions in Indo-Gangetic Plains of India - Mishra, Ajay Kumar; Shinjo, Hitoshi; Jat, Hanuman Sahay; Jat, Mangi Lal; Kumar Jat, Raj; Funakawa, Shinya (Frontiers in Sustainable Food Systems, 2024)
This study evaluates the impact of conservation agriculture (CA) on soil carbon sequestration and crop productivity in the Indo-Gangetic Plains, focusing on short-term effects over 3 and 5 years. Conducted at two distinct sites, Karnal and Samastipur, the research compares zero tillage, permanent raised beds, and conventional tillage systems across diverse cropping patterns. Initial findings after 3 years showed no significant differences in carbon and nitrogen stocks at Karnal, while Samastipur’s maize-mustard-mungbean rotation on permanent raised beds showed increased carbon stocks. Notably, after 5 years, significant differences in soil carbon stocks emerged at both sites, with improved organic matter input indicated by coarse particulate organic matter (cPOM) formation. The study confirms the potential of POXC and POC as early indicators for carbon sequestration in CA systems, highlighting the role of CA practices in enhancing soil health and crop productivity sustainably.